Safety and Efficacy of Mepolizumab in Patients with Eosinophilic Granulomatosis with Polyangiitis - Pradhan, Ravi Ranjan; Nepal, Gaurav; Mandal, Shobha (Pulmonary Medicine, 2019)
Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare form of vasculitis disorder which involves multiple organ systems and is characterized by asthma, pulmonary infiltrates, sinusitis, neuropathy, and peripheral eosinophilia. It also has an effect on the heart, skin, kidneys, and gastrointestinal tract. Interlukin-5 (IL-5) is involved in maturation and activation of eosinophil, the production of which is increased in the EGPA. Treatments of EGPA are limited to systemic corticosteroids and immunomodulators. These drugs are associated with significant side effects. Besides this, the response of patients to these drugs may be disappointing. Frequent relapses, the need for long-term medium-to-high-dose glucocorticoid therapy, and failure to achieve remission are not uncommon findings. There is a need for noble agents that could reduce frequent relapses and the dose of systemic glucocorticoids and maintain a sustained remission without significant side effects. Mepolizumab is IL-5 antagonist and may have value in treating patients with EGPA. Therefore, we did a systematic review to evaluate the efficacy and safety of mepolizumab in patients with EGPA.